1988
DOI: 10.1149/1.2095904
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry of Uranium and Plutonium in Molten LiCl ‐ NaCl ‐ CaCl2 ‐ BaCl2 : I . Reduction of U(III) to Uranium Metal1

Abstract: The electrochemical reduction of U(III) to uranium metal in molten normalLiCl‐normalNaCl‐CaCl2‐BaCl2 electrolyte was investigated, using cyclic voltammetry. The reaction is reversible and controlled by diffusion mass transfer, both at low‐carbon steel and molybdenum electrodes. The rate increased with UCl3 concentration up to about 3.4 mole percent and with temperature over the range of 435°–528°C. Standard potentials ranged from −1.07 to −1.50V vs. normalAg/normalAgCl ; the U(III) diffusion coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Store et al 61 reported two consecutive voltammograms of PbCl 2 -LiCl-KCl that differ significantly from each other, but none of these studies commented on the reason for the variances. In addition, Poa et al, 29 who studied systems with high concentrations of U and Pu in molten salts, reported a discrepancy between results using the same experimental setup. In the majority of the studies, however, no information about the reproducibility of the measurements has been found.…”
Section: Resultsmentioning
confidence: 97%
“…Store et al 61 reported two consecutive voltammograms of PbCl 2 -LiCl-KCl that differ significantly from each other, but none of these studies commented on the reason for the variances. In addition, Poa et al, 29 who studied systems with high concentrations of U and Pu in molten salts, reported a discrepancy between results using the same experimental setup. In the majority of the studies, however, no information about the reproducibility of the measurements has been found.…”
Section: Resultsmentioning
confidence: 97%
“…The number of the transferred electron, n, was calculated to be 2.6-3.0 from the relation between the cathodic peak potential (E c p ) and the cathodic halfpeak potential (E c p 2 ) as shown in (Eq. (2)) [20] at scan rate between 0.05 and 1 V/s.…”
Section: Resultsmentioning
confidence: 99%
“…Various investigations have been carried out on the electrochemistry of the U(III)/U couple in molten LiCl-KCl eutectic [5][6][7][8][9][10][11][12][13][14][15][16]. In all studies [5][6][7][8][9][10][11][12][13][14] oxide materials (glasses and alumina) were used in the construction of electrochemical cell, but our experiments showed that these materials interacted with LiCl-KClUCl 3 melt due to the high affinity of uranium to oxygen.…”
Section: Introductionmentioning
confidence: 99%